Comparative analysis of several linear controllers with developed feedback controllers for DSTATCOM. (2019) - Elnady, A.
This paper analyses the performance of the distribution static compensator (DSTATCOM) for two linear controllers and two developed state feedback controllers. The paper clarifies how the DSTATCOM controls the reactive power using the quadrature current, Iq, and the active power for adjusting its DC voltage across its capacitor, Vdc . The PI and PID controllers are employed as an example for a linear controller. The linear quadratic regulator (LQR) and a novel structure and formulation of the decoupled state feedback controller, SFC, are adopted as tools for the pole placement so as to control the operation of the DSTATCOM. A comprehensive analysis for these four controllers is given to justify the merits and demerits of each controller. In addition, the proposed state feedback is also compared to an integral sliding mode controller, SMC, to prove its superior performance. Finally, three different applications for the developed state feedback controller are demonstrated to prove the meritorious performance of this developed control scheme for the operation of the DSTATCOM to control the reactive power and mitigate voltage quality problems within distribution systems.